The impact of health on economic growth: A panel approach of selected Western Balkans countries - Cvetanoska, Marijana; Trpeski, Predrag (Faculty of Economics Pale, 2021)
Economists have long been interested in explaining cross-country differences in economicgrowth by focusing on the determinants of growth. One of the most important contributors to growthis human capital. Health constitutes an important form of human capital too and therefore should notbe neglected. Therefore, the aim of this study is to analyse the relationship between health andeconomic growth. We use life expectancy at birth as an indicator of health, and GDP per capita as anindicator for economic growth. We use data for Western Balkan countries that are not part ofEuropean Union, but aspire to be. The data on the variables used in this empirical study is based onWorld Bank Development Indicators. Countries which are subject of analysis are: North Macedonia,Albania, Serbia, Bosnia and Herzegovina, and Montenegro. Across countries, GDP per capita is highlycorrelated with health. Using panel data analysis, this study provided evidence of the impact of humancapital, i.e. health on economic growth in the selected Western Balkan countries. The study showedthat the impact of health is statistically significant and has a positive impact on economic growth inthe selected countries. As a consequence, we conclude that health should be considered as animportant factor that contributes to the economic performance of Western Balkans’ economies. In thehealth sector, the main challenge is to continue to make progress towards achieving health systemobjectives, namely improving population health status by increasing investments in health.
Keywords: economic growth, GDP per capita, health, life expectancy at birth, Western Balkans